Retail Sukuk from the Perspective of Maqashid Al-Sharia - Cholili, Azwar; Muslih, Imam; Muttaqin, Muh. Syaukin; Maghfiroh, Anisatul; Arifin, Sirajul (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
One of the products offered in the capital market is sharia bonds (sukuk). This is a huge attraction for businesses and governments. By raising funds through the issuance of sukuk, companies and governments have access to significant resources that can be used to increase lending to Islamic financial institutions. The need for the business world and government to build infrastructure and expand private businesses is one way to activate alternative sources of financing for the business world and national economic development. In addition, there is a need for legal clarification regarding the actions of market players and the differences that exist between investors and speculators. According to Islamic law, sukuk falls into the category of muamalah, where its Sharia compliance allows innovation while adhering to the goals, principles, and objectives of Sharia economics. Utilizing sukuk to achieve beneficial objectives according to Islamic economic principles does not mean immediately enacting sharia without a clear legal basis